Developing Culture-Based Tourism Attractions through Pentahelix Collaboration in Satupam Tourism Village - Ellan Jaya Adi Putra; Luisa Cornelia Wijaya; Jessica Natania Vinata; Steven Ryan Tedja; Budi Setiawan (Politeknik Sahid, 2026)
This study analyzes the development of culture-based tourist attractions in Satupam Tourism Village, South Tangerang, by focusing on the implementation of the pentahelix collaboration model. Utilizing a qualitative method with a Participatory Rural Appraisal (PRA) approach, the research involves active collaboration between academics, tourism managers, and local communities. The findings reveal that pentahelix collaboration has been initiated through the academic sector's role in providing legal assistance and human resource training, as well as local government support via a formal Memorandum of Understanding (MoU). A significant cultural transformation is identified within the Rumpun Betawi community, where the